Muscular strength of knee extensors and flexors and bilateral and ipsilateral ratio in elite male kickboxers - Maly, T.; Mala, L.; Zahalka, F.; Hank, M.; Simkova, M. (Archives of Budo, 2017)
Background and Study Aim: Kickboxing is combat sport where the form of combat are strikes, performed by hands and legs. The aim of this study was verification of the hypothesized that the non-preferred leg of elite male kickboxers would have lower knee extensor and flexor strength and there will be a higher incidence of bilateral and unilateral strength deficit.